Pendampingan Perancangan Produksi Film Dokumenter Penghijauan Desa Pasir Biru, Sumedang Sebagai Branding Kampus Merdeka - Salsa Solli Nafsika; Zakarias S Soeteja; Tri Karyono; Trianti Nugraheni; Sukanta Sukanta; Dedi Warsana; Defrizaldi Defrizaldi; Jihan Winarti (Institut Pertanian Bogor, 2025)
This service is a support activity for exchange students program “pertukaran Mahasiswa Merdeka” (PMM) from various provinces through environmental campaigns using artistic video content to deal with the impact of infrastructure development and accessibility that affects changes in airflow and heat distribution. This environmental impact is the main focus for independent exchange student participants in realizing social contribution programs through reforestation activities in desa Pasir Biru Rancakalong Sumedang. Through this reforestation program, we aim to increase environmental awareness, educate the public about the importance of protecting ecosystems, and reduce the impact of climate change resulting from National Infrastructure Development. So it is hoped that environmental campaigns through documentary films can inspire and motivate the wider community to participate in environmental conservation efforts. The research method uses a Base Research Design based on Documentary Film Production in the Reforesting Program involving research targets and community service targets student of the Pertukaran Mahasiswa Merdeka (PMM) programs as the development of aesthetic skills in creating documentary films, service partners from the Department of Environment and Forestry (DLHK) , plant seed cultivation entrepreneurs, village governance, and all elements of society. The output of this service is in the form of a sustainable impact felt by the community and a documentary film from the development of artistic production design through video content to elaborate the brand image of the Kampus Merdeka Program in the environmental and temperature revitalization campaign in the area.